EFFECT OF FUNGICIDES, TRICHODERMA AND PLANT EXTRACTS ON MYCELIAL GROWTH OF THIELAVIOPSIS PARADOXA, UNDER IN VITRO CONDITION - RANJANA CHAKRABARTY; G. C. ACHARYA; T. C. SARMA (The Bioscan, 2013)
Stem bleeding disease caused by Thielaviopsis paradoxa is one of the major diseases of coconut and is prevalent in almost all the coconut growing countries. The present study was carried out to test the efficacy of antagonist, fungicides and plant extracts in inhibiting the pathogen, under in vitro condition. Thielaviopsis was isolated from young lesion of affected coconut palm of CPCRI, RC, Kahikuchi, Guwahati. Among the three species of Trichoderma tested so far, T. viride was found to be the most effective with 61.62% inhibition followed by T. harzianum and T. virens with 60.80 and 59.49 per cent inhibition, respectively, over control after 96h of incubation period. The fungicides, Calixin (Tridemorph 80EC) @ 0.3% showed 100 per cent inhibition over control whereas Ridomil MZ-72, Blitox-50 and Bavistin showed 92.00, 91.55 and 91.44 per cent inhibition over control after 144h of incubation, respectively, Among the forty five plant extracts tested, the aqueous extract (10%) of Allium sativum, exerted 100 per cent inhibition of the pathogen over control after 48h, 72h and 96h of incubation compared to other extracts